The asymmetric effects of interest rate changes on household consumption: a case for South Africa - How household consumption reacts to changes in the interest rate - Fikizolo, Siphosethu Lucia (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management